The Effect of Vitamin D Supplementation in Children With Asthma: A Meta-Analysis - Hao, Meiqi; Xu, Ruoxin; Luo, Nachuan; Liu, Miaowen; Xie, Junping; Zhang, Wenxiong (Frontiers in Pediatrics, 2022)
Background: An increasing number of studies have suggested that vitamin D can be used to treat childhood asthma, but its clinical effects are still unclear. We conducted this meta-analysis to examine the latest estimates of the effectiveness and safety of using vitamin D to treat childhood asthma. Methods: The PubMed, The Cochrane Library, ScienceDirect, Embase, Scopus, Ovid MEDLINE, Web of Science and Google Scholar databases were searched for randomized controlled trials (RCTs) describing vitamin D supplementation interventions for asthmatic children. Asthma exacerbation, vitamin D levels, the predicted percentage of forced expiratory volume in the first second (FEV1%) and adverse effects (AEs) were analyzed as the main outcome measures. Results: After screening, eight RCTs with 738 children were included. Compared with placebos, vitamin D supplementation had a stronger effect on serum vitamin D levels (mean difference (MD) = 13.51 [4.24, 22.79], p = 0.004). The pooled results indicated that no significant changes were found between the groups in asthma control, as measured by adopting the following indicators: asthma exacerbation (risk ratio (RR) = 0.92 [0.68, 1.25], p = 0.60); Childhood Asthma Control Test (CACT) scores (MD = 0.15 [-0.43, 0.74], p = 0.61); hospitalizations for asthma exacerbation (RR = 1.20 [0.48, 2.96], p = 0.70); acute care visits (RR = 1.13 [0.77, 1.65], p = 0.63); steroid use (RR = 1.03 [0.41, 2.57], p = 0.95); and fractional exhaled nitric oxide (FeNO) (MD =-3.95 [-22.87, 14.97], p = 0.68). However, vitamin D supplementation might reduce the FEV1% (MD = -4.77 [-9.35, -0.19], p = 0.04) and the percentage of predicted forced vital capacity (FVC%) (MD =-5.01 [-9.99, -0.02], p = 0.05) in patients. Subgroup analysis revealed no difference in AEs between the two groups. Conclusions: Vitamin D supplementation significantly increased patients’ serum vitamin D levels, but it had no benefit for asthma control. However, vitamin D supplementation might reduce patients’ lung function. It is essential to systemically search for more large-scale, rigorous and well-designed RCTs to fully confirm these conclusions.